2017
DOI: 10.1177/0954407017723761
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered magnetorheological dampers for motorcycle suspensions

Abstract: Dampers are the parts of suspensions which improve the ride comfort and the safety of vehicles including motorcycles. Magnetorheological dampers are very attractive for motorcycle suspensions, because of their controllable properties and their fast responses. Considerable energy is wasted owing to the energy dissipation by dampers encountering road irregularities and accelerating processes during everyday use of motorcycles. In addition, the current magnetorheological suspension systems depend on the power sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Overall, the aforementioned findings indicate that the techniques to recover suspension energy have considerable potential for converting vehicle vibration energy, which is normally wasted as heat, into electricity. Therefore, various types of regenerative shock absorbers have been proposed, such as linear electromagnetic ones (Zhang, 2010; Zhu et al , 2012), ball-screw ones (Liu et al , 2017; Kim et al , 2016), rack–pinion ones (Guo et al , 2016; Chen et al , 2018) and hydraulic-electric ones (Chen et al , 2018; Fang et al , 2013a, b). However, Gupta et al showed that the power density of electromagnetic-coil shock absorbers is insufficient for vehicles, meaning that they cannot provide enough damping (Gupta et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the aforementioned findings indicate that the techniques to recover suspension energy have considerable potential for converting vehicle vibration energy, which is normally wasted as heat, into electricity. Therefore, various types of regenerative shock absorbers have been proposed, such as linear electromagnetic ones (Zhang, 2010; Zhu et al , 2012), ball-screw ones (Liu et al , 2017; Kim et al , 2016), rack–pinion ones (Guo et al , 2016; Chen et al , 2018) and hydraulic-electric ones (Chen et al , 2018; Fang et al , 2013a, b). However, Gupta et al showed that the power density of electromagnetic-coil shock absorbers is insufficient for vehicles, meaning that they cannot provide enough damping (Gupta et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers studied the roll, 13–15 pitch, 16,17 elimination torsion, 18 and vibration isolation characteristics 19,20 and stability 21,22 in the air suspension field. Energy saving is a goal for many scholars in different fields of automotive engineering such as the transmission system, 2326 driving cycle, 2729 suspension system, 3032 magnetorheological dampers, 33 energy harvesting, 34 and so on. Sun et al 30 declared that the interconnected system causes energy reduction due to not using compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The developed MR damper was tested on the test rig, the experimental results showed that the developed MR damper can not only achieve the ability of the relative displacement sensing, which can serve as displacement sensor, but also produce large controllable damping force. Chen and Liao [15], [16] designed a type of function-integrated MR damper, which integrated a power source, a displacement sensor and a damper into one device. This structure would produce the electrical energy from the working environment and can feedback the dynamic data to the control system.…”
Section: Introductionmentioning
confidence: 99%